2013
DOI: 10.1258/ar.2012.120420
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two different vacuum-assisted breast biopsy systems: Mammotome® system 11G/8G vs. ATEC® system 12G/9G

Abstract: Both biopsy systems meet all requirements for daily practice and confirm the diagnosis of suspicious microcalcifications. The ATEC(®) system was observed to be faster but this difference of about 250 s might not be relevant in daily practice. The Mammotome(®) system provides a better histologic quality of tissue samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
(25 reference statements)
1
3
0
Order By: Relevance
“…The present study showed that the occurrence of hematoma was 11.4% (39/343). This result was similar to that reported by Vargas et al (8) but less than that reported by some previous studies (6,9).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study showed that the occurrence of hematoma was 11.4% (39/343). This result was similar to that reported by Vargas et al (8) but less than that reported by some previous studies (6,9).…”
Section: Discussionsupporting
confidence: 91%
“…The size of the specimen was about (0.3-0.5 cm) × (1.8-2.0 cm) for each sample. The mean number of samples obtained from a single insertion was 10 (range, [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The procedure lasted 10-30 min.…”
Section: Us-guided Excisional Vabmentioning
confidence: 99%
“…VACB proves to be a method that eliminates or to a large extent limits these disadvantages [11]. It is an efficient, minimally invasive, relatively inexpensive procedure with a good cosmetic effect, and has a low complication rate [12]. Similar to minimally invasive techniques used in the treatment of other organs, VACB, in some cases, can be an alternative to a more extended surgical procedure [13].…”
Section: Discussionmentioning
confidence: 99%
“…The preserved architecture also facilitates easier interpretation on histopathology examination, avoiding the crushing and fragmentation artefacts seen in fragmented tissue cores. 20 A review of the current literature, however, shows that no studies have been made to compare the accuracy between fragmented cores and en-bloc specimens. Further studies are warranted to establish any possible improvements in diagnosis.…”
Section: Quality Of Specimensmentioning
confidence: 99%